Masculinist impulses Toomer, Hurston, Black writing, and modernity - Grant, Nathan 1957- (University of Missouri Press, 2004)
"In Masculinist Impulses, Nathan Grant begins his analysis of African American texts by focusing on the fragmentation of values of black masculinity - free labor, self-reliance, and responsibility to family and community - as a result of slavery, postbellum disfranchisment, and the ensuing necessity to migrate from the agrarian South to the industrialized North. Through examinations of novels that deal with black male selfhood, Grant demonstrates the ways in which efforts to alleviate the most destructive aspects of racism ultimately reproduced them in the context of the industrialized city."